Refinement of Midpoint and Trapezoid Type Inequalities for Multiplicatively Convex Functions - Amel Berhail; Badreddine Meftah (Sahand Communications in Mathematical Analysis)
In this study, we first establish two new identities for multiplicative differentiable functions. Based on these identities, we derive the midpoint and trapezoid type inequalities. The acquired outcomes improve and refine upon Khan and Budak's findings. At the conclusion, some applications to special means are provided.